Perioperative Minimal Induction Therapy: A Further Step toward More Effective Immunosuppression in Transplantation - Alessia Gennarini; Paolo Cravedi; Maddalena Marasà; Annalisa Perna; Giovanni Rota; Mario Bontempelli; Silvio Sandrini; Giuseppe Remuzzi; Piero Ruggenenti (Journal of Transplantation)
Dual induction with low doses of rabbit anti-human thymoglobulin (RATG) and basiliximab effectively and safely prevented allograft rejection in high-risk renal transplant recipients. To assess whether treatment timing affects efficacy and tolerability, in this single-center, matched-cohort study, we compared posttransplant outcomes in 25 patients and 50 gender-, age-, and treatment-matched reference patients induced with the same course of 7 daily RATG infusions (0.5 mg/kg/day) started before or after engraftment, respectively. All subjects received basiliximab (20 mg) before and 4 days after transplantation, withdrew steroids within 6 days after surgery, and were maintained on steroid-free immunosuppression with cyclosporine and mycophenolate mofetil or azathioprine. Over 12 months after transplant, 1 patient (4%) and 13 reference patients (26%) had acute rejection episodes. One patient and 5 reference-patients required dialysis therapy because of delayed graft function. In all patients circulating CD4+ and CD8+ T lymphocytes were fully depleted before engraftment. Both treatments were well tolerated. In kidney transplantation, perioperative RATG infusion enhances the protective effect of low-dose RATG and basiliximab induction against graft rejection and delayed function, possibly because of more effective inhibition of early interactions between circulating T cells and graft antigens.